INVESTIGATING THE ACT OF DESIGN IN DISCHARGE CONCEPT USING PMRI - Lestariningsih Lestariningsih; Muhammad Anwar; Agus Mulyanto Setiawan (Journal on Mathematics Education, 2015)
The goal of this research is to investigate the act of design in discharge concept using Pendidikan Matematika Realistik Indonesia (PMRI) approach with Lapindo's Mud phenomenon as a context. Design research was chosen as method used in this research that consist of three phases, namely preparing for the experiment, teaching experiment,Â  and retrospective analysis. Based on the result of investigating from findings and the data obtained in this research, it can be concluded that the use of instructional design using PMRI can support students' understanding in learning the concept of discharge. Observing activities Lapindo mud photos, watching videos Lapindo mud, observing miniature discharge of Lapindo mud, volume of water and time of data collection are needed, and finding discharge of Lapindo mud are conducted in this research.